Effects of Grain Boundary Angles on Initial Deformation of 304 Austenitic Stainless Steel under Nanoindentation: A Molecular Dynamics Simulation - Longlong Yang; Kun Sun; Weixiang Peng; Xuejie Li; Liang Zhang (Crystals, 2022)
Nitrogen-containing 0Cr19Ni10 (304 NG) austenitic stainless steel plays a significant role in Generation IV reactor pressure vessels. The structure and properties of 304 NG are heavily influenced by the grain boundaries (GBs), especially the initial mechanical response and dislocation evolutions. Hence, in this paper, we carried out molecular dynamics (MD) simulations to investigate the effects of the GB angles on the initial deformation of 304 models under nanoindentation. It is found that the GB angle has great effects on the mechanical properties of 304 NG. With the GB angles changing from 90° to 150°, the values of Young’s modulus and maximum shear stress first decrease and then increase due to decreasing of the interaction among the GBs and the grain interiors (GIs) and the smoother shape of GBs. The hardening region slope decreases rapidly result from the GB angles changing the grain size on the both sides, which fully fits the Hall–Petch relationship. After the dislocations reaching the GBs along the slip system, the dislocation piles-up on the GBs at first, and then GBs serve as a source of dislocation and emit dislocation to free surface with the depth of nanoindentation increasing. This work provides a better understanding on the angle effects of GBs in materials.